Land degradation and intensified livestock and crop production in the Ethiopian highlands - Mohamed-Saleem, M.A.; Mwendera, E.J. (South African Society of Animal Science, 1996)
The Ethiopian highlands are ecologically heterogenous and densely populated by humans and animals. Due to the high human population pressure and large herds of livestock on small farm areas, continuous overgrazing of natural grasslands is common. In attempts to meet the increasing food and feed demands of large human and livestock populations, respectively, farmers are cultivating more land permanently, grazing lands have been encroached and many traditional farming systems have broken down. Apart from keeping a mix of animals, particularly oxen to supply farm power requirements, farmers in the highlands cultivate a complex mix of crops for subsistence. ILRI's collaborative research with national partners, NGOs and other IARCs in the Ethiopian highlands has focussed on generating environmentally safe technologies for improving the welfare of resource-poor smallholder farmers who depend on crop-livestock production systems across the fragile highland ecologies of East Africa.